Acculturative stress level and its contributing factors among international postgraduate students at Universiti Putra Malaysia, Serdang - Ye, Huadan (2017)
Introduction: Acculturative stress among international students is a serious issue. Oversea students face several problems because of the linguistic and cultural differences in their host country. It is important to understand their acculturative stress level and its contributing factors, in order to develop plans and policies and attract international students as well as ease their stay at UPM.